2020
DOI: 10.1186/s13293-020-00324-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadal hypertension in male Sprague-Dawley rats is renin-angiotensin system-dependent: role of endogenous androgens

Abstract: Background: Acutely, testosterone (TES) and other androgens are efficacious vasodilators, both in vitro and in vivo; however, their long-term effects on arterial blood pressure (BP) remain unclear. It was hypothesized that endogenous androgens exert long-term anti-hypertensive effects on systemic BP through a combination of genomic and nongenomic effects to enhance vasodilation of the systemic vasculature. Methods: The long-term effects of endogenous TES and exogenous TES replacement therapy (TRT) on BP were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
(118 reference statements)
0
3
2
1
Order By: Relevance
“…This mechanism occurs via inhibition of aldosterone synthase activity and cytochrome P-450 side-chain cleavage (P450scc) activity, and ACTH-stimulated c-AMP accumulation in the zona glomerulosa cells. Also, endogenous androgens (testosterone) exert anti-hypertensive effects that appear to involve non-genomic and possibly genomic mechanism(s), resulting in reductions in RAS expression in the kidney and enhanced systemic vasodilation in male rats (Hanson et al 2020). Instead, the present study indicated a negative association between blood aldosterone and seminal plasma testosterone in infertile camels.…”
Section: Discussioncontrasting
confidence: 60%
“…This mechanism occurs via inhibition of aldosterone synthase activity and cytochrome P-450 side-chain cleavage (P450scc) activity, and ACTH-stimulated c-AMP accumulation in the zona glomerulosa cells. Also, endogenous androgens (testosterone) exert anti-hypertensive effects that appear to involve non-genomic and possibly genomic mechanism(s), resulting in reductions in RAS expression in the kidney and enhanced systemic vasodilation in male rats (Hanson et al 2020). Instead, the present study indicated a negative association between blood aldosterone and seminal plasma testosterone in infertile camels.…”
Section: Discussioncontrasting
confidence: 60%
“…Interestingly, androgens also appear to have a protective role in this strain. Castrated Sprague-Dawley males exhibited increased blood pressure levels and RAS activity [ 19 ], which supports the role of testosterone in the regulation of the RAS and, consequently, blood pressure. In addition, these changes returned to normal with testosterone treatment [ 19 ].…”
Section: Normotensive Rodent Modelsmentioning
confidence: 75%
“…Normotensive models Dog ↑ BP in males [14] Fowl ↑ BP and vascular plaque in males [15] WKY rat ↑ BP in males [16] ↑ NO bioavailability in females [17] Sprague-Dawley rat ↑ BP in males ↑ NO bioavailability in females [18] Sex hormones affecting RAS [19] Non-genetic hypertensive models Sprague-Dawley rat (+Ang II infusion)…”
Section: Strain/model Description Of Sex Differences Possible Molecul...mentioning
confidence: 99%
“…Sex hormones play an important role in regulating blood pressure in both men and women ( Jiménez et al 2018 , Hester et al 2019 ). Androgens, especially testosterone, play a key role in cell growth ( Hanson et al 2020 , Stone & Stachenfeld 2020 ). The characteristics of testosterone synthesis and metabolism involve increased protein synthesis, which is essential for normal and hypertrophic growth of cardiomyocytes ( Carbajal-García et al 2020 , Troncoso et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%